A influência do modelo de triplice hélice no grau de maturidade de inovação: um estudo de caso em empresas participantes do projeto PRÓ-INOVA/NAGI no estado do RIO GRANDE DO NORTE - Nunes, Benilton Medeiros (2013)
Public investments in the development of innovation in the country, either through the rigging of public universities, either through public announcements of the promotion, increased dramatically in recent years. To analyze the efficiency and effectiveness of the use of public resources is especially in times of austerity, essential for the development of a country. In this context, this research aims to identify the influence of public investments to promote innovation in the degree of maturity of innovative companies in the state of the RN. Another goal is to identify the regional influence from the installation site - capital or countryside, in the performance of the companies studied in the degree of innovation. The theoretical basis of the understanding of the scope of the concept of innovation and its determination for the purposes of this study. Typology, degree of innovation, evaluation methodologies and mechanisms to support innovation : Still on the theme of innovation additional concepts that help the reader to a greater understanding, such as are presented. Following is approached conceptualization of the triple helix, highlighting the concepts advocated by Etzkowitz and Leydesdorff, Salomon and Silva and Ipiranga, Freitas and Paiva, among others. With regard to methodological aspects, we propose a descriptive, exploratory and explanatory research quantitative and qualitative approach with the target audience group of companies served by INOVA PRO- NAGI design - multi-institutional action from a public resource called FINEP promotes the development of innovative companies in the State of Rio Grande do Norte - in 2013. The research should provide reflection and understanding of the influence of public investment in innovation, which by means of qualitative predictive variables associated with quantitative method to explain which variables are significant variations in the degree of maturity of enterprises studied